( x + 1) + (x + 4) + (x + 7) + ......... + (x + 28) = 156
=> (x+x+...+x)+(1+4+7+...+28)=156
=>10x + 145 = 156
=> 10x=156-145=11
=> x= 11/10
\(\left(x+1\right)+\left(x+4\right)+\left(x+7\right)+...+\left(x+28\right)=156\)
\(\Rightarrow x+1+x+4+x+7+...+x+28=156\)
\(\Rightarrow10x+1+4+7+...+28=156\)
\(\Rightarrow10x+\frac{\left(28+1\right).\left[\left(28-1\right)\div3+1\right]}{2}=156\)
\(\Rightarrow10x+145=156\)
\(\Rightarrow10x=156-145\)
\(\Rightarrow10x=11\)
\(\Rightarrow x=11\div10\)
\(\Rightarrow x=1,1\)